PREPARATION AND CHARACTERIZATION OF PbSe THIN FILMS BY CHEMICAL BATH DEPOSITION - Anuar Kassim; Tan Wee Tee; Dzulkefly Kuang Abdullah; Md. Jelas Haron; Ho Soon Min; Shanthi Monohorn; Saravanan Nagalingam (Jurnal Kimia (Journal of Chemistry), 2010)
PbSe thin films were grown onto glass substrates by chemical bath deposition method. Structure and surfacemorphology of thin films were characterized by X-ray diffraction and scanning electron microscopy. The band gapenergy and type of optical transition were determined from optical absorbance data. The deposition parameters wereoptimized to obtain good quality of thin films. X-ray diffraction indicates that the films have cubic structure. TheSEM micrograph showed the films do not cover the glass substrate completely and consisted of irregular shapedgrains. The films show good optical properties with high absorption in the visible region and the band gap value wasestimated to be 1.3 eV.